#### Answer

$-(x+2)$

#### Work Step by Step

$\frac{x^{2}-4}{2-x}=\frac{(x+2)(x-2)}{2-x}=\frac{(x+2)(x-2)}{-(x-2)}=\frac{x+2}{-1}\times\frac{x-2}{x-2}=-(x+2)\times1=-(x+2)$

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

$-(x+2)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.